The Insulin-like Growth Factor-1 Binding Protein Acid-labile Subunit Alters Mesenchymal Stromal Cell Fate - Fritton, J. Christopher (American Society for Biochemistry and Molecular Biology, 2010)
Age-related osteoporosis is accompanied by an increase in marrow adiposity and a reduction in serum insulin-like growth factor-1 (IGF-1) and the binding proteins that stabilize IGF-1. To determine the relationship between these proteins and bone marrow adiposity, we evaluated the adipogenic potential of marrow-derived mesenchymal stromal cells (MSCs) from mice with decreased serum IGF-1 due to knockdown of IGF-1 production by the liver or knock-out of the binding proteins. We employed 10–16-week-old, liver-specific IGF-1-deficient, IGFBP-3 knock-out (BP3KO) and acid-labile subunit knock-out (ALSKO) mice. We found that expression of the late adipocyte differentiation marker peroxisome proliferator-activated receptor γ was increased in marrow isolated from ALSKO mice. When induced with adipogenic media, MSC cultures from ALSKO mice revealed a significantly greater number of differentiated adipocytes compared with controls. MSCs from ALSKO mice also exhibited decreased alkaline-phosphatase positive colony size in cultures that were stimulated with osteoblast differentiation media. These osteoblast-like cells from ALSKO mice failed to induce osteoclastogenesis of control cells in co-culture assays, indicating that impairment of IGF-1 complex formation with ALS in bone marrow alters cell fate, leading to increased adipogenesis.